Nocardia farcinica Meningitis Masquerading as Central Nervous System Metastasis in a Child With Cerebellar Pilocytic Astrocytoma. Issue 6 (August 2015) - Davis, Jennifer; Kreppel, Andrew J.; Brady, Rebecca C.; Jones, Blaise; Stevenson, Charles B.; Fouladi, Maryam; Hummel, Trent R.
<x xml:space="preserve">Abstract</x> Juvenile pilocytic astrocytoma, the most common pediatric central nervous system (CNS) neoplasm, characteristically displays an indolent growth pattern and rarely demonstrates metastatic dissemination. Reports of infections mimicking CNS metastatic disease are also rare and can impact treatment. We report the youngest known case of a child with a CNS Nocardia farcinica infection who had a known cerebellar pilocytic astrocytoma, review other infections that may masquerade as CNS neoplasms, and discuss N. farcinica CNS infections.